2021
DOI: 10.21153/jtlge2021vol12no2art982
|View full text |Cite
|
Sign up to set email alerts
|

‘…having people that will help you, that know the ropes and have walked that road before you’: How does first in family status impact graduates in the employment field?

Abstract: Increasing competitiveness in the graduate employment field combined with growing numbers of degree bearing applicants means that gaining employment after completing university studies can be a lengthy and complex undertaking. This is even more the case for students who do not have ready access to the social or family capital often required for successful employment, such as those who are first in their family to attend university. This article reveals hidden tensions within the post-graduation employment mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…We also know that non-traditional students face challenges with regard to the transition into university (Briggs et al, 2012), such as experiencing feelings of uncertainty and pressure in the making of education choices, feelings of isolation and disconnectedness when starting university, and decreased levels of success while at university. In terms of transitioning out of university, researchers have shown that non-traditional students often lack the necessary personal and relational capital needed to successfully compete in a hyper competitive graduate employability market (O'Shea et al, 2021). The responses of participants in this project echo many of the findings from such research.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…We also know that non-traditional students face challenges with regard to the transition into university (Briggs et al, 2012), such as experiencing feelings of uncertainty and pressure in the making of education choices, feelings of isolation and disconnectedness when starting university, and decreased levels of success while at university. In terms of transitioning out of university, researchers have shown that non-traditional students often lack the necessary personal and relational capital needed to successfully compete in a hyper competitive graduate employability market (O'Shea et al, 2021). The responses of participants in this project echo many of the findings from such research.…”
Section: Discussionmentioning
confidence: 65%
“…There is evidence that students believe that the more education they have the better, which can encourage them to believe their degree/s are a ticket to the career of their choice (Lock & Kelly, 2020). Such beliefs can lead some students to miss out on opportunities known to be associated with enhanced employability (O'Shea et al, 2021). Overall, we have reason to presume that an expectations gap about employability teaching and learning might well exist, but there is little definitive evidence articulating either that such a gap exists or, if it does, what the characteristics of this gap might be.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The theory can be utilized to explain how the conscious state and regular engagement can strengthen individual attributes. Self-motivation, developing positive attributes, proactiveness and sincerity in actions are the driving factors for individuals, and these also directly relate to upbringing and family environment (O’Shea et al, 2021).…”
Section: Social Cognitive Career Theory and Employability Attributesmentioning
confidence: 99%
“…The research available emphasises the positive, and even vital, aspects of extracurricular participation for university students, especially regarding their career and personal development, as well as their sense of belonging and well-being on our campuses (Burke et al, 2005;Clark et al, 2015;Milner et al, 2016;Stuart et al, 2011). However, how ECA participation impacts students with disabilities has not been similarly scrutinised, with the few studies focusing on this issue highlighting the positive impacts of participation at the high school level (O'Shea et al, 2021;Palmer et al, 2017;Wehman et al, 2014). There is also little evidence of previous studies that examine how decisions made at the strategic and policy level reflect the importance of the employability skills taken from these opportunities for students with disabilities.…”
Section: Introductionmentioning
confidence: 99%